Quranic Arabic : from its Hijazi origins to its classical reading traditions - Van Putten, Marijn (Studies in Semitic languages and linguistics, 2022)
"What was the language of the Quran like, and how do we know? Today, the Quran is recited in ten different reading traditions, whose linguistic details are mutually incompatible. This work uncovers the earliest linguistic layer of the Quran. It demonstrates that the text was composed in the Hijazi vernacular dialect, and that in the centuries that followed different reciters started to classicize the text to a new linguistic ideal, the ideal of the arabiyyah. This study combines data from ancient Quranic manuscripts, the medieval Arabic grammarians and ample data from the Quranic reading traditions to arrive at new insights into the linguistic history of Quranic Arabic"--